Tragic Optimism as a Buffer Against COVID-19 Suffering and the Psychometric Properties of a Brief Version of the Life Attitudes Scale - Leung, Mega M.; Arslan, Gökmen; Wong, Paul T. P. (Frontiers in Psychology, 2021)
The Life Attitudes Scale (LAS) was designed to measure tragic optimism (TO)—a distinct type of optimism that could generate hopeless hope even in dire situations according to existential positive psychology (PP 2.0). This study explains why only a faith-based TO could serve as a buffer against suffering at the Nazi death camps as well as the global coronavirus disease 2019 (COVID-19) pandemic. In study 1, the results showed that the factorial structure of a 15-item LAS-Brief (LAS-B), which is a short measure of TO, replicated the original structure of the 32-item long version. The five factors (i.e., affirmation, acceptance, courage, faith, and self-transcendence) provided a good data model fit statistics for LAS-B; the measure had adequate-to-strong internal and latent construct reliability estimates. In study 2, the buffering effect of TO on the association between suffering experiences during COVID-19 and life satisfaction in adults was examined. The results of the studies were consistent with our hypothesis that TO as measured by LAS-B serves as a buffer against the impact of COVID-19 suffering on life satisfaction.